N11 Adherence, self-care and illness perception in patients with Inflammatory Bowel Disease – a qualitative study. (30th January 2023) - Ljungström, E; Eberhardson, M; Hjortswang, H; Pihl Lesnovska, K
Abstract: Background: Medical treatment (MT) is key in the management of Inflammatory Bowel Disease (IBD, ulcerative colitis [UC] and Crohn's disease [CD]) and non-adherence is a barrier to treatment efficacy. Approximately 30 % of patients with IBD is non-adherent to MT. Self-care is defined as; the process of maintaining health through health-promoting practices and managing illness. Adherence is an important part of self-care in IBD. Illness perception relates to understanding disease and potential consequences. The aim of this study is to add deeper understanding of adherence and non-adherence as part of self-care and explore the links to illness perception and self-efficacy in patients with IBD. Methods: Semi-structured interviews were conducted face-to-face with 15 IBD patients (5 CD, 9 UC, 1 IBD-U, Table 1 ) at a university IBD-clinic in Sweden. Patients were invited to ensure richness of data and maximum variation of disease duration, age, and sex. Interviews were recorded, transcribed verbally, and analysed with inductive, latent content analysis. Results: Analysis resulted in three main categories and ten subcategories. The first category, Disease Perception, included the observation that a majority of the informants monitors disease through bowel symptoms. However, perception of severe illness was linked to low daily function. Most informants used stress reduction and diet to reduce symptoms. Some informants struggled with acceptance of disease while others seem to have reached higher acceptance. Fear related to disease was expressed, e.g., colonoscopies, cancer and progress of disease. The second category, Health Care Perception, showed that informants highly desired a personal connection with the doctor. Some informants expressed trust issues due to delayed diagnosis, kindreds' bad experiences from health care or emotional trauma related to disease onset or care. Unmet need of information mainly concerned the health care system, the diagnosis and MT. The third category, Treatment Perception, included the informants' ambivalence towards MT, where worries of potential harm from MT was central. Preferences on administration of MT was a factor that influenced adherence. Many informants perceived that non-medical strategies are more or equally important as MT to decrease symptom burden. Conclusion: The findings add understanding of reasons for adherence and non-adherence to MT and demonstrates the complex mechanisms behind this phenomenon. The informants' evaluation of risk and benefit with MT covers considerations that are not entirely medically established. This highlights the importance of a trustful dialogue and shared decision making between patient and health care provider in order to increase adherence.